PENGARUH STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN LOYALITAS KARYAWAN HOTEL SATRIA WISATA PAREPARE - Mukarrama, Mukarrama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of human resource management strategies in increasing employee loyalty at Hotel Satria Wisata Parepare. The data collection techniques in this study were observation, interviews, and questionnaires. The population in this study were employees of Hotel Satria Wisata Parepare, so the total population in this study was 26 people and used a census sample. The research method used is the descriptive quantitative method. The results showed that there was a positive and significant influence between human resource management strategies in increasing employee loyalty at Hotel Satria Wisata Parepare. Thus the hypothesis is proven. A human resource management strategy that provides added value is one of the main benchmarks for the success of a business. Thus, in terms of resources, the business strategy is to get the maximum added value that can optimize competitive advantage. This means that if the company wants to get employees with high loyalty, it should be mastered.Human Resource Management Strategy